Evidence for charged B meson decays to a(1)(+/-)(1260)pi(0) and a(1)(0)(1260)pi(+/-) - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2007)
We present measurements of the branching fractions for the decays B±→a1±(1260)π0 and B±→a10(1260)π± from a data sample of 232×106 BB̄ pairs produced in e+e- annihilation through the Υ(4S) resonance. We measure the branching fraction B(B±→a1±(1260)π0)×B(a1±(1260) →π-π+π±)=(13.2±2.7±2.1)×10-6 with a significance of 4.2σ, and the branching fraction B(B±→ a10(1260)π±)×B(a10(1260)→π-π+π0)=(20.4±4. 7±3.4)×10-6 with a significance of 3.8σ, where the first error quoted is statistical and the second is systematic. © 2007 The American Physical Society.